Advanced facilitation strategies tools & techniques to master difficult situations - Bens, Ingrid (San Francisco Jossey-Bass, 2005)
From Ingrid Bens, the author of the best-selling book Facilitating with Ease!, comes the next-step resource for project leaders, managers, community leaders, teachers, and other facilitators who want to hone their skills in order to deal with complex situations. Advanced Facilitation Strategies is a field guide that offers practical strategies and techniques for working with challenging everyday situations. These proven strategies and techniques are based on experience gleaned from hundreds of facilitated activities in organizations of all sizes and in all sectors.
Includes bibliographical references (p. 241-244).
Keywords: Teams in the workplace